Backdraft [videorecording (DVD)] - Russell, Kurt; Baldwin, William, 1963-; Glenn, Scott, 1942-; Leigh, Jennifer Jason, 1962-; DeMornay, Rebecca, 1963-; Sutherland, Donald, 1935-; De Niro, Robert; Howard, Ron, 1954- (Universal Home Video, 1998)
Stephen McCaffrey and his younger brother Brian are two feuding siblings carrying on an heroic family tradition in the Chicago fire department. Stephen is so relentless that he drives Brian out of firefighting and into arson investigation. Assisting arson investigator Donald Rimgale, Brian becomes involved in a puzzling series of arson attacks, each ignited by explosive phenomena known as backdrafts. Before the smoke clears, love affairs are rekindled and lives are shattered as the McCaffrey brothers fight to resolve their differences and solve the mystery.